Mechanical characterization of cement and gypsum based mortars with nano and micro silica particles for passive fire protection of steel structures - Monteiro, Eduardo Celso Cruz (2022)
Dissertação de Mestrado em Engenharia Civil apresentada à Faculdade de Ciências e Tecnologia